Analytisch versus holistisch oder: Warum Erwachsene im Fremdsprachenunterricht den Erklärungen eine besondere Bedeutung beimessen? - Czarnecka, Małgorzata (Glottodidactica, 2013)
The objective of this paper is to answer the following question: Why do adults attach special importance to presentation of explicit rules in foreign language teaching? The foregoing poses the question if and to what extent the ability to think analytically is supported at school.And furthermore: to what extent it has effect on the students’ learning style and subsequently on the process of foreign language acquisition. The author has also conducted a brief pilot study.